2022
DOI: 10.3389/fimmu.2022.891822
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Curcumin and Curcuma longa Extract in the Treatment of Arthritis: A Systematic Review and Meta-Analysis of Randomized Controlled Trial

Abstract: BackgroundModern pharmacological research found that the chemical components of Curcuma longa L. are mainly curcumin and turmeric volatile oil. Several recent randomized controlled trials (RCT) have shown that curcumin improves symptoms and inflammation in patients with arthritis.MethodsPubmed, Cochran Library, CNKI, and other databases were searched to collect the randomized controlled trials (RCTs). Then, the risk of bias of RCTs were assessed and data of RCTs were extracted. Finally, RevMan 5.3 was utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 118 publications
1
28
0
1
Order By: Relevance
“…The serum triglyceride levels in the HFDC group showed significantly decreased levels versus those of the HFD group. Our results were in agreement with previous studies [ 40 42 ] whose studies confirmed a significant effect of curcumin in reducing serum TG concentrations, suggesting the hypotriglyceridemic activity of curcumin. Also, Seo et al [ 43 ] emphasized that curcumin significantly lowered the hepatic activities of fatty acid synthase, beta-oxidation, plasma FFA, cholesterol, and triglyceride concentrations.…”
Section: Discussionsupporting
confidence: 94%
“…The serum triglyceride levels in the HFDC group showed significantly decreased levels versus those of the HFD group. Our results were in agreement with previous studies [ 40 42 ] whose studies confirmed a significant effect of curcumin in reducing serum TG concentrations, suggesting the hypotriglyceridemic activity of curcumin. Also, Seo et al [ 43 ] emphasized that curcumin significantly lowered the hepatic activities of fatty acid synthase, beta-oxidation, plasma FFA, cholesterol, and triglyceride concentrations.…”
Section: Discussionsupporting
confidence: 94%
“…[30][31][32] Curcumin, a plant-derived FDA-approved drug with low toxicity has been proved to be beneficial in improving DAS28, american college of rheumatology/european league against rheumatism, visual analog scale, western ontario and mcMaster universities osteoarthritis index) scoring of rheumatoid arthritic and osteoarthritic patients. 33 Present study is the first to highlight the analgesic activity of curcumin also in alleviating CHIKV-induced acute/chronic arthritis within mouse model. Significant increase in leg pain-threshold level and decrease in feet-swelling of CHIKV-infected mice after treatment (pre, co, and post) with curcumin demonstrated its analgesic, prophylactic, and anti-inflammatory effect against CHIKV-induced acute/chronic arthritic manifestation.…”
Section: Discussionmentioning
confidence: 73%
“…HD of 2000 mg/kg curcumin was most effective against alleviating pain and feet‐swelling. CHIKV infection has been reported to trigger rapid innate immune response by producing pro‐inflammatory cytokines that might lead to articular cartilage loss and bony erosion in affected joints, as documented among Thai and Indian patients 30,34,35 . CHIKV replication in joint tissues induced expression of pro‐osteoclastogenic cytokines, IL‐6, nuclear factor kappa B (NF‐κB), TNF‐α, IL‐1β, and receptor activator of nuclear factor kappa‐Β ligand (RANKL) among Singaporean and Thai patients that promoted bone resorption and arthritic manifestation 30,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple NPs including plant extracts from traditional medicines are known to have significant anti-inflammatory effects by regulating of cytokine production and can be used for several inflammatory diseases such as RA, atopic dermatitis and IBD ( Ghasemian et al, 2016 ; Luo et al, 2020 ; Wu et al, 2021 ; Zeng et al, 2022 ). Although the traditional knowledge about medicinal NPs is progressively getting lost, traditional plants are still commonly used in the Pacific region ( Rageau and Schmid, 1973 ; Bourdy et al, 1992 ; Whistler, 1992 ).…”
Section: Introductionmentioning
confidence: 99%